Icterus pectoralis (spot-breasted oriole) - Realo, Ian (Animal Diversity Web, 2013)
Spot-breasted orioles are found down the Pacific Coast of Mexico and Central America, reaching from southern Mexico to Costa Rica. Found at a range of altitudes, from below 500 m in Mexico and Costa Rica, and up to 1500 m in El Salvador and Honduras. There are four recognized subspecies of spot-breasted orioles. The I. p. carolynae subspecies is native to southern Mexico, Pacific Coast of Guerrero and Oaxaca. I. p. pectoralis is native to southeast Mexico and east Oaxaca, central Chiapas south to Tonalá. The I. p. guttulatus subspecies is native to southeast Mexico south to arid valleys of Guatemala, Honduras, and northwestern Nicaragua. Finally, the I. p. espinachi subspecies is native to southwestern Nicaragua and northwestern Costa Rica. Spot-breasted orioles have been introduced to the United States in southeast Florida. (Jaramillo and Burke, 1999; del Hoyo, et al., 2011)
Keywords: 2014 UMBC Phage Hunters